Experience of diagnosis and surgical treatment of cardiac myxomas - R.M. Vitovskyi; V.V. Isaіenko; A.R. Vitovskyi; O.A. Pishchurin; V.V. Grabarchuk; O.V. Satmari (Кардіохірургія та інтервенційна кардіологія)
The aim – to present the one-centre experience of surgical treatment with сardiac myxomas (CM) and features of the course of this disease. Materials and methods. During the period from January 1, 1969 to January 1, 2023, 1015 patients were operated for primary heart tumors. CM were found in 902 (88.9 %) patients, of which 793 (87.9 %) cases were myxomas of the left atrium. The age of CM patients ranged from 3 to 79 years (on average 48.4 ± 3.4 years), of which 653 (72.4 %) were in the age from 31 to 60 years. Malignant tumors were observed in 70 (6.9 %) cases. Results. Surgery of valvular lesions was performed in 75 (8.3 %) patients: in 15 (1.7 %) cases – valve prosthesis, in 55 (6.1 %) cases – repair surgery (25 – mitral correction, 30 – tricuspid valves, respectively) with a positive functional effect. 328 (36.3 %) and 77 (8.5 %) patients with CM had heart failure of III and IV functional classes NYHA, respectively, which often required urgent surgery. Hospital mortality in recent years was 0.2 % in the surgical treatment of CM. Conclusions. The issues of optimal tactics for patients with CM consist of urgent diagnosis and surgical intervention, which ensures the effectiveness of treatment of CM, which is confirmed by the data of long-term results. Patient survival up to 20 years was 79.7 %.